Effect of Gender on Coagulation Functions: A Study in Metastatic Colorectal Cancer Patients Treated with Bevacizumab, Irinotecan, 5-Fluorouracil, and Leucovorin. (21st August 2014) - Bilir, Cemil; Engin, Hüseyin; Temi, Yasemin Bakkal
Abstract : Introduction. We designed this study to evaluate how coagulation parameters are changed in metastatic colorectal cancer (mCRC) patients treated with bevacizumab, irinotecan, 5-fluorouracil, and leucovorin (FOLFIRI). Methods. A total of 48 mCRC patients who initially received bevacizumab with FOLFIRI were eligible for this study. Thirty-four patients were analyzed at baseline and on the 4th, 8th, and 12th cycles of chemotherapy. Results. There were 19 male and 15 female patients. Baseline characteristics of the groups were similar, but women had better overall survival than men (14 months versus 12 months, P = 0.044 ). D-dimer levels decreased significantly after the 12th cycle compared with baseline in men but not in women. Men and women had increased levels of serum fibrinogen at the early cycles, but these increased fibrinogen levels continued after the 4th cycle of chemotherapy only in women. In addition, serum fibrinogen levels did not significantly change, but aPTT levels decreased in men. Discussion. The major finding of this study is that bevacizumab-FOLFIRI chemotherapy does not promote changes in the coagulation system. If chemotherapy treatment and the possible side effects of FOLFIRI-bevacizumab treatment are well managed, then alterations of the coagulation cascade will not have an impact on overall survival and mortality.